Undelivered electricity as an indicator of the effects of automation in the 10 kV network PD ED Belgrade - Vrcelj, Nada S; Ivković, Sanja; Perić, Jelena; Đorđevic, Dragan; Janjić, Tijana; Ćupić, Branislav; Ivanov, Aleksandar; Minić, Saša (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
The paper discusses the effects of automation in the 10 kV PD ED Belgrade valorized through undelivered electricity. In the paper it was observed the parts of the network for which it was possible to reconstruct the events of the past. Calculations undelivered electricity were carried out for the period prior to the implementation of recloser in remote control system and during the period of probation system. A significant reduction in the duration of the fault, and thus undelivered electricity in automated network, indicates an increase in the reliability level after the implementation in the system SCADA SN.